Upaya Hukum Terhadap Praktik Pembuangan Limbah Nuklir - Aksan, Lanang Dwi; Anwar, Arman; Waas, Richard Marsilio (Faculty of Law Universitas Pattimura, 2024)
Japan is an industrial country that uses nuclear as its main energy source. In 2011 an earthquake and tsunami hit Japan in Fukushima, which caused a nuclear disaster. This causes the plant to produce contaminated air every day, which is then stored in large tanks and Japan states that this is not a sustainable solution. Japan's plans to dump processed air waste from the Fukushima nuclear power plant into the sea have raised concerns and anger at home and abroad. The international regulatory framework can be found in the UN Convention on the Law of the Sea and the 1972 London Convention. Japan is one of the parties involved in these two conventions. Countries involved in these conventions must issue legal regulations to prevent and reduce marine contamination due to waste disposal. The research uses research methods with a normative juridical research type. The problem approaches used are the statutory approach, conceptual approach and case approach. The sources of legal materials used are primary, secondary and tertiary legal materials. procedures for collecting legal materials and processing legal materials through literature using qualitative descriptive analysis. Based on the results of the research conducted, it can be concluded that the case of dumping Fukushima nuclear waste into the sea is in the spotlight because of its detrimental impact on the marine environment and public health. Japan is forced to dump nuclear waste into the sea due to limited storage space. This action raised concerns not only at the local level, but also internationally. Japan is expected to take responsibility for these actions and overcome their negative impacts. Countries have efforts and obligations to enforce laws to repair marine damage due to pollution. They must implement regulations and take the necessary efforts to prevent, reduce and control marine pollution based on international law. Damage recovery measures are required, including requests for compensation as the responsibility of the party who caused the pollution. State responsibility in international law emphasizes that countries that cause harm to other countries must be held responsible and make appropriate reparations to return things to normal.